Implementing guidelines to routinely prevent chronic vascular disease in primary care: the Preventive Evidence into Practice cluster randomised controlled trial. Issue 12 (11th December 2015) - Harris, Mark Fort; Parker, Sharon M; Litt, John; van Driel, Mieke; Russell, Grant; Mazza, Danielle; Jayasinghe, Upali W; Del Mar, Chris; Lloyd, Jane; Smith, Jane; Zwar, Nicholas; Taylor, Richard; et al.
Abstract : Objective: To evaluate an intervention to improve implementation of guidelines for the prevention of chronic vascular disease. Setting: 32 urban general practices in 4 Australian states. Randomisation: Stratified randomisation of practices. Participants: 122 general practitioners (GPs) and practice nurses (PNs) were recruited at baseline and 97 continued to 12 months. 21 848 patient records were audited for those aged 40–69 years who attended the practice in the previous 12 months without heart disease, stroke, diabetes, chronic renal disease, cognitive impairment or severe mental illness. Intervention: The practice level intervention over 6 months included small group training of practice staff, feedback on audited performance, practice facilitation visits and provision of patient education and referral information. Outcome measures: Primary: 1. Change in proportion of patients aged 40–69 years with smoking status, alcohol intake, body mass index (BMI), waist circumference (WC), blood pressure (BP) recorded and for those aged 45–69 years with lipids, fasting blood glucose and cardiovascular risk in the medical record. 2. Change in the level of risk for each factor. Secondary: change in self-reported frequency and confidence of GPs and PNs in assessment. Results: Risk recording improved in the intervention but not the control group for WC (OR 2.52 (95% CI 1.30 to 4.91)), alcohol consumption (OR 2.19 (CI 1.04 to 4.64)), smoking status (OR 2.24 (1.17 to 4.29)) and cardiovascular risk (OR 1.50 (1.04 to 2.18)). There was no change in recording of BP, lipids, glucose or BMI and no significant change in the level of risk factors based on audit data. The confidence but not reported practices of GPs and PNs in the intervention group improved in the assessment of some risk factors. Conclusions: This intervention was associated with improved recording of some risk factors but no change in the level of risk at the follow-up audit. Trial registration number: Australian and New Zealand Clinical Trials Register (ANZCTR): ACTRN12612000578808, results.